Using heat as a tracer to estimate spatially distributed mean residence times in the hyporheic zone of a riffle‐pool sequence. Issue 6 (21st June 2013) - Naranjo, Ramon C.; Pohll, Greg; Niswonger, Richard G.; Stone, Mark; Mckay, Alan
Abstract : [1] Biochemical reactions that occur in the hyporheic zone are highly dependent on the time solutes that are in contact with sediments of the riverbed. In this investigation, we developed a 2‐D longitudinal flow and solute‐transport model to estimate the spatial distribution of mean residence time in the hyporheic zone. The flow model was calibrated using observations of temperature and pressure, and the mean residence times were simulated using the age‐mass approach for steady‐state flow conditions. The approach used in this investigation includes the mixing of different ages and flow paths of water through advection and dispersion. Uncertainty of flow and transport parameters was evaluated using standard Monte Carlo and the generalized likelihood uncertainty estimation method. Results of parameter estimation support the presence of a low‐permeable zone in the riffle area that induced horizontal flow at a shallow depth within the riffle area. This establishes shallow and localized flow paths and limits deep vertical exchange. For the optimal model, mean residence times were found to be relatively long (9–40.0 days). The uncertainty of hydraulic conductivity resulted in a mean interquartile range (IQR) of 13 days across all piezometers and was reduced by 24% with the inclusion of temperature and pressure observations. To a lesser extent, uncertainty in streambed porosity and dispersivity resulted in a mean IQR of 2.2 and 4.7 days, respectively. Alternative conceptual models demonstrate the importance of accounting for the spatial distribution of hydraulic conductivity in simulating mean residence times in a riffle‐pool sequence. Key Points: reduction of uncertainty in residence times given temperature and pressure Mixing of vertical and horizontal flow controls mean residence times Long residence times coincide with low hydraulic conductivity